2018
DOI: 10.3389/fnbeh.2018.00057
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Salience of Anger and Aggression in Female Adolescents With Borderline Personality Disorder—A Script-Based fMRI Study

Abstract: Background: Anger and aggression belong to the core symptoms of borderline personality disorder. Although an early and specific treatment of BPD is highly relevant to prevent chronification, still little is known about anger and aggression and their neural underpinnings in adolescents with BPD.Method: Twenty female adolescents with BPD (age 15–17 years) and 20 female healthy adolescents (age 15–17 years) took part in this functional magnetic resonance imaging (fMRI) study. A script-driven imagery paradigm was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…However, some findings also show a hypoactivation in the orbitofrontal cortex (OFC) and the anterior cingulate cortex (ACC), but strong activity in amygdala (Fulwiler et al, 2012; Siep et al, 2018). A meta-analysis study confirmed enhanced activation in the left amygdala to angry stimuli (Bertsch et al, 2018; Krauch et al, 2018). These controversies might be due to the fact that amygdala activity is related to initiation of fear, while activation of the orbitofrontal cortex is involved in the fear extinction (Milad and Rauch, 2007; Siep et al, 2018).…”
Section: Fmri Data On Basic Emotionsmentioning
confidence: 79%
“…However, some findings also show a hypoactivation in the orbitofrontal cortex (OFC) and the anterior cingulate cortex (ACC), but strong activity in amygdala (Fulwiler et al, 2012; Siep et al, 2018). A meta-analysis study confirmed enhanced activation in the left amygdala to angry stimuli (Bertsch et al, 2018; Krauch et al, 2018). These controversies might be due to the fact that amygdala activity is related to initiation of fear, while activation of the orbitofrontal cortex is involved in the fear extinction (Milad and Rauch, 2007; Siep et al, 2018).…”
Section: Fmri Data On Basic Emotionsmentioning
confidence: 79%
“…Results of studies assessing neural correlates of ED in adolescents with BPD are heterogeneous. Comparing female adolescents with BPD and healthy controls, Krauch et al ( 304 ) found increased activation in the left posterior insula and left dorsal striatum as well as in the inferior frontal gyrus and parts of the mentalizing network. This suggests an enhanced emotional reactivity to interpersonal threat- or rejection-related situations early in the development of BPD.…”
Section: Resultsmentioning
confidence: 99%
“…It noteworthy that these regions are components of the fronto-limbic circuit and are related to a broad range of cognitive and emotional processes, which have been described as being altered in BPD. These processes have been studied as dysfunctional traits in this disorder and include emotional dysregulation, impulsiveness, aggressive behavior, suicidal tendencies, and self-destructive behavior (59). Some of these regions are a part the default mode network, which is usually related to processes that involve thought formation by self as autobiographical memory, future planning, and inferring one's mental states and those of others (60), which are all processes involved in social cognition (61).…”
Section: Discussionmentioning
confidence: 99%